Distribuição espacial de metais na água, sedimentos e macrófitas aquáticas em um rio do Semiárido brasileiro - Oliveira, Camila Tâmires Alves (2019)
River pollution by metals is of concern because of its persistence in the environment, the incorporation and biological expansion in the food chain and the toxic effects on organisms, including humans. Thus, this study hypothesized that the concentration of metals in the water and sediments varied along the river basin according to the use and occupation of the same and that the concentrations of metallic elements in these abiotic compartments of the aquatic ecosystem are different from each other. The objectives of our study were to infer about the possible sources of metallic elements from the analysis of land use and occupation; to evaluate the concentrations of Cu, Fe, Mn, Zn, Zn, Cd, Cr, Ni and Pb metals in the water and sediments of the Apodi-Mossoró River and to determine which physical and chemical variables affect the availability and distribution of metals. For this, we collected water and sediment samples at 14 sampling sites along the Apodi-Mossoró River, located in the state of Rio Grande do Norte, Brazil. The results showed that the concentrations of metallic elements in the more urbanized areas and in the estuarine area presented higher values of metals than the distant sites of urban centers. The levels of metals were higher in the sediments than in the water, due to the influence of the organic matter that causes the deposition of the metals in the sediments. The metal Fe was the element with the highest values obtained, with a mean of 6580.39 mg.kg-1 in the sediments and of 0.7 mg.L-1 in the water, while the Cd showed lower concentrations, with a mean of 7.12 mg.kg-1 in the sediments and 0.02 mg.L-1 in the water. None of the physical and chemical variables of water, such as nutrients, pH, electrical conductivity, salinity, total dissolved solids, dissolved oxygen, organic and inorganic carbon showed influence on the concentration of metals in the river water. In this way, it is possible to conclude that the concentrations of metals along the watershed varied according to the use and occupation of the same and that the concentrations of metals were higher in the sediments than in the water column, probably due to the influence of the organic matter